Simptomatologie en anatomie van gleufstam ('legno riccio') by die wingerdstok (Vitis) - Kriel, G. J. le R. (Gabriel Jacobus le Roux) (Stellenbosch : Stellenbosch University, 2012)
Thesis MSc(Agric)--Stellenbosch University, 1973.